Ethiopia Employment and Jobs Study - World Bank (World Bank, Washington, DC, 2019)
As many developing countries around the world, Ethiopia is faced with the challenge of generating employment for a rapidly-growing and youthful population. Ethiopia’s working age population, currently estimated at 54.7 million, is projected to grow by two million per year over the coming decade and this growth is unlikely to slow any time soon given persistently high fertility rates. The fast-growing labor force, combined with improving education levels, the drive for industrialization, and the increased scarcity of agricultural land, will have far-reaching consequences for the social and economic structure of the country, the nature of work, and labor mobility and the growth of town and cities. This jobs and employment study focus on employment dynamics in Ethiopia between 1999 and 2016. Using data from a variety of sources, mainly the labor force surveys (1999, 2005, and 2013) and the Ethiopia socioeconomic surveys (2012, 2014, and 2016), the report looks at what workers in Ethiopia are doing, how employment has changed over the past fifteen years, and how inter- and intra-sectoral employment dynamics have been associated with productivity and economic growth. The report also aims to identify which groups have been doing well on the employment front and which groups are lagging. To add context and depth, the quantitative analysis has been complemented by a qualitative research study on rural youth employment, conducted in April and May 2017 in 16 woredas in the four most populous regions of Ethiopia.